Assessment of the glycemic and lipidemic profile of patients suffering from bipolar disorder. - Shah, Farid ullah; Naeem, Awais; Naim, Fahad; Ahmad, Wasim (International Journal of Endorsing Health Science Research, 2022)
Background: Impaired glycemic profile and cognitive impairment are generally associated with bipolar disorders. Patients on long-term use of psychotropic drugs are more prone to other medical abnormalities etc. The study's objective was to assess the glycemic and lipidemic profiles of patients with bipolar disorder reported at a tertiary care hospital in the Khyber Pakhtunkhwa-Pakistan. Methodology: This was a cross-sectional study conducted in a private hospital in Khyber Pakhtunkhwa from January 2020 to June 2021. A total of 400 patients were enrolled in the study, and the sample size was calculated using a WHO calculator. Blood tests were performed for high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), total cholesterol (TC), fasting glucose, and triglycerides (TG). Results: Of the total 400 enrolled patients, 84.0% (n=336) had a diagnosis of bipolar disorder while rest of the 16.0% (n=64) had Schizophrenia. No statistical difference was found in the metabolic parameters following the primary diagnosis. As for pharmacological parameters, patients with bipolar disorders were receiving more psychiatric medicines than schizophrenic patients with a p-value < 0.001. Conclusion: It is concluded that the levels of HDL, LDL, and total cholesterol were significantly elevated in the manic condition compared to the Euthymic phase and by improving their glycemic and lipidemic profiles, cognitive dysfunction might be rectified, and functioning can be improved.